The journey of remdesivir: from Ebola to COVID-19 - Joe Pardo; Ashutosh M Shukla; Gajapathiraju Chamarthi; Asmita Gupte (BioExcel Publishing Ltd, 2020)
Countries around the world are currently fighting the coronavirus disease 2019 (COVID-19) pandemic, which is caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV- 2). SARS-CoV-2 is a betacoronavirus, belonging to the same genus as severe acute respiratory syndrome (SARS)-CoV and Middle East respiratory syndrome (MERS)-CoV. Currently, there are no proven antiviral therapies for COVID-19. Numerous clinical trials have been initiated to identify an effective treatment. One leading candidate is remdesivir (GS-5734), a broad-spectrum antiviral that was initially developed for the treatment of Ebola virus (EBOV). Although remdesivir performed well in preclinical studies, it did not meet efficacy endpoints in a randomized trial conducted during an Ebola outbreak. Remdesivir holds promise for treating COVID-19 based on in vitro activity against SARS-CoV-2, uncontrolled clinical reports, and limited data from randomized trials. Overall, current data are insufficient to judge the efficacy of remdesivir for COVID-19, and the results of additional randomized studies are eagerly anticipated. In this narrative review, we provide an overview of Ebola and coronavirus outbreaks. We then summarize preclinical and clinical studies of remdesivir for Ebola and COVID-19.